Implant-abutment gap versus microbial colonization: Clinical significance based on a literature review - Passos, Sheila Pestana; Gressler May, Liliana; Faria, Renata; Özcan, Mutlu; Bottino, Marco Antonio [UNESP] (Wiley, 2013)
Microorganisms from the oral cavity may settle at the implant-abutment interface (IAI). As a result, tissue inflammation could occur around these structures. The databases MEDLINE/PubMed and PubMed Central were used to identify articles published from 1981 through 2012 related to the microbial colonization in the implant-abutment gap and its consequence in terms of crest bone loss and osseointegration. The following considerations could be put forward, with respect to the clinical importance of IAI: (a) the space present at the IAI seems to allow bacterial leakage to occur, in spite of the size of this space; (b) bacterial leakage seems to occur at the IAI, irrespective of the type of connection. More studies are necessary to clarify the relationship between leakage at IAI and abutment connection designs; (c) losses at the peri-implant bone crests cannot be related to the IAI size, since few studies have shown no relationship. Also, the microbial leakage at the IAI cannot be related to the bone crest loss, since there are no articles reporting this relationship; remains controversial the influence of the IAI position on the bone crest losses. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 101B: 1321-1328, 2013. Copyright © 2013 Wiley Periodicals, Inc.
Keywords: bone loss; implant-abutment connection; implant-abutment gap; microbial leakage; osseointegration; Bone loss; Connection designs; Literature reviews; Microbial colonization; Osseointegration; Tissue inflammation; Bacteria; Bone; Abutments (bridge); alveolar bone loss; bacterial growth; bone density; bone regeneration; dental abutment; in vitro study; inflammation; Medline; microbial colonization; mouth cavity; nonhuman; osteolysis; review